Varicella zoster virus-associated anterior uveitis in a seronegative adult without a history of chickenpox - Mine I (Dove Medical Press, 2015)
Izumi Mine, Sho Ishikawa, Masaru TakeuchiDepartment of Ophthalmology, National Defense Medical College, Tokorozawa City, Saitama, JapanAim: The aim of this report was to present a case of varicella zoster virus (VZV)-associated anterior uveitis, which developed in an adult who was seronegative for anti-VZV antibodies.Case presentation: A 66-year-old male patient was referred to the National Defense Medical College, Tokorozawa City, Japan with iridocyclitis in his right eye. On examination, intraocular pressure was 30 mmHg in the right eye, and biomicroscopy revealed ciliary injection, corneal epithelial edema, mutton fat keratic precipitates, flare, and infiltrating cells in the anterior chamber. Serological tests were negative for anti-VZV antibodies, but VZV-DNA copies of 1.28×107 copies/mL were detected by quantitative reverse transcriptase polymerase chain reaction using the aqueous humor obtained from the right eye. Iridocyclitis was reduced by administration of oral valaciclovir in addition to corticosteroid eye drops, and serum anti-VZV antibodies were first detected after 4 months’ administration. When ocular inflammation was resolved after 6 months, VZV-DNA could not be detected in the aqueous humor any more.Conclusion: VZV-associated uveitis may develop in an adult with undetectable serum anti-VZV antibodies. Multiplex polymerase chain reaction of the aqueous humor is the key investigation necessary for the diagnosis in such cases.Keywords: varicella zoster virus, VZV, zoster sine herpete, multiplex polymerase chain reaction, uveitic glaucoma